2018
DOI: 10.1016/j.jot.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

MC3T3 infiltration and proliferation in bovine trabecular scaffold regulated by dynamic flow bioreactor and augmented by low-intensity pulsed ultrasound

Abstract: BackgroundLow-intensity pulsed ultrasound (LIPUS) has been used in both basic research and clinical settings for its therapeutic potential in promoting tissue healing. Clinical data has shown that LIPUS can accelerate fresh fracture healing. However, the treatment for aging osteoporosis and non-union is still unclear. In addition, the mechanism of ultrasound promoted bone healing has remained unknown.ObjectiveIt is proposed that noninvasive ultrasound treatment can enhance local fluid flow within the tissue to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“… 62 In addition to tumor ablation, ultrasound was proven to enhance bone regeneration since it could enhance the mRNA level of vascular endothelial growth factor A (VEGF-A) and stimulate cartilage cell proliferation, thus accelerating the maturation of newly formed bone and expediting cell mineralization. 63 , 64 With in-depth research, this technique was extended to the infection field for the clinical treatment of bone defects and severe bacterial infection. 27 , 31 , 65 Crasto et al 66 fabricated novel liposome-rhBMP-2 nanocomplexes that can release rhBMP-2 after exposure to nonthermogenic clinical diagnostic ultrasound.…”
Section: External Stimuli-responsive Bone Therapy and Regenerationmentioning
confidence: 99%
“… 62 In addition to tumor ablation, ultrasound was proven to enhance bone regeneration since it could enhance the mRNA level of vascular endothelial growth factor A (VEGF-A) and stimulate cartilage cell proliferation, thus accelerating the maturation of newly formed bone and expediting cell mineralization. 63 , 64 With in-depth research, this technique was extended to the infection field for the clinical treatment of bone defects and severe bacterial infection. 27 , 31 , 65 Crasto et al 66 fabricated novel liposome-rhBMP-2 nanocomplexes that can release rhBMP-2 after exposure to nonthermogenic clinical diagnostic ultrasound.…”
Section: External Stimuli-responsive Bone Therapy and Regenerationmentioning
confidence: 99%
“…In interbody fusion, another critical determinant is the new bone formation around the intervertebral fusion cage. , A bioactive material should have the capacity to stimulate biological response to realize effective osteogenesis. , The regenerative ability of the material could be improved by optimizing composition or incorporating bioactive ions that play a pivotal role in osteogenic process. In our previous study, we demonstrated that the presence of CS incorporated into PEEK could effectively release the bioactive Ca 2+ and Si 4+ ions which exerted a positive influence on the osteogenic differentiation of preosteoblasts in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been numerous studies on utilizing ultrasound for enhancing antibacterial performance or osteogenic capability of orthopedic implants, most of them have focused solely on single function, either antibacterial ability or osteogenic capacity. However, it is desirable to investigate the performance of an ultrasound-responsive strategy in enhancing both antibacterial and osteogenic capability of orthopedic implants. Furthermore, the selection of sonosensitizers plays a critical role in achieving targeted and successful treatment.…”
Section: External Stimuli-responsive Strategies For Surface Modificat...mentioning
confidence: 99%